The Competing Politics of Austrian Glocalization: Covid-19, Crime and (Anti-)Racism (Glocalism: Journal of Culture, Politics and Innovation, 2020)
Based on a carefully contextualised discussion of discursive and semiotic contributions to public debate in Austria during the politically charged summer of 2020, this article captures ideologically different, at times mutually opposed glocalizing strategies. The social sites and entanglement of “the global” and “the local” examined are the following: a parliamentary address in which neo-nationalist rhetoric is framed by global points of reference; local appropriations of the Black Lives Matter movement for the purposes of symbolic protest against public monuments commemorating problematic regional histories; and recent public debates in Austria that illustrate the glocalization of everyday politics. In each example, global contexts provide crucial momentum for the articulation of local concerns and mobilisations. The ensuing analysis helps illuminate some of the distinctly transnational, enabling conditions for ideological contest in Austria today. In methodological terms, the discussion demonstrates that an understanding of locally specific appropriations of a diversity of global flows demands ethnographic sensitivity, historical contextualisation, and local knowledge.
Keywords: Austria; nationalism; Black Lives Matter; glocalizing strategies, politics of representation